Feasibility study of analgesia via epidural versus continuous wound infusion after laparoscopic colorectal resection1. Issue 3 (19th December 2012) - Boulind, C. E.; Ewings, P.; Bulley, S. H.; Reid, J. M.; Jenkins, J. T.; Blazeby, J. M.; Francis, N. K.
Abstract: Background: With the adoption of enhanced recovery and emerging new modalities of analgesia after laparoscopic colorectal resection (LCR), the role of epidural analgesia has been questioned. This pilot trial assessed the feasibility of a randomized controlled trial (RCT) comparing epidural analgesia and use of a local anaesthetic wound infusion catheter (WIC) following LCR. Methods: Between April 2010 and May 2011, patients undergoing elective LCR in two centres were randomized to analgesia via epidural or WIC. Sham procedures were used to blind surgeons, patients and outcome assessors. The primary outcome was the feasibility of a large RCT, and all outcomes for a definitive trial were tested. The success of blinding was assessed using a mixed‐methods approach. Results: Forty‐five patients were eligible, of whom 34 were randomized (mean(s.d.) age 70(11·8) years). Patients were followed up per‐protocol; there were no deaths, and five patients had a total of six complications. Challenges with capturing pain data were identified and resolved. Mean(s.d.) pain scores on the day of discharge were 1·9(3·1) in the epidural group and 0·7(0·7) in the WIC group. Median length of stay was 4 (range 2–35, interquartile range 3–5) days. Mean use of additional analgesia (intravenous morphine equivalents) was 12 mg in the WIC arm and 9 mg in the epidural arm. Patient blinding was successful in both arms. Qualitative interviews suggested that patients found participation in the trial acceptable and that they would consider participating in a future trial. Conclusion: A blinded RCT investigating the role of epidural and WIC administration for postoperative analgesia following LCR is feasible. Rigorous standard operating procedures for data collection are required. Copyright © 2012 British Journal of Surgery Society Ltd. Published by John Wiley & Sons, Ltd. Abstract : A RCT investigating pain relief is feasible